Herpes Zoster In Teenagers: Case Report - Prakoeswa, Flora Ramona Sigit; Rosyida, Hindun Luthfia (Chakra Brahmanda Lentera Institute, 2023)
Background: Herpes Zoster (HZ) is a reactivation of the Varicella Zoster Virus (VVZ), which is characterized by an acute unilateral vesicular eruption grouped with radicular pain around the dermatome. The incidence of HZ increases with age and is rare in children. The prevalence of HZ in children can occur if they have a history of primary intrauterine infection, are immunocompromised, and are infected with varicella in the first year of life. Methods: The research design used a case study on one of the patients at the PKU Muhammadiyah Hospital Surakarta Polyclinic. The instruments include informed consent and demographic data questionnaires. Results: Ms B, 15 years old, came to the Skin and Venereology Clinic, PKU Muhammadiyah Surakarta Hospital on December 28, 2022 with complaints of itching and heat, a lesion in the form of multiple clustered vesicles, round in shape, with a size of 0.3- 0.5 cm above the skin, erythematous, unilateral, not crossing the midline, the age of the cysts in one group is the same. Still, with other groups, it is not the same; the skin between groups is normal. Treatment was given acyclovir 4x800 mg per day taken orally for five days, triamcinolone 4 mg/day, compressed NaCl 15 minutes 2x daily, calamine lotion 2x daily on intact lesions and mupirocin calcium on open wounds. Conclusion: Maintaining the body's immune system and managing stress, as well as getting the varicella vaccine/measles vaccine, can prevent the occurrence of shingles